Pengaruh PenerapanStrategi Belajar Aktif tipe Practice Rehearsal pairs Terhadap Kemampuan Pemahaman Konsep Matematis Mahasiswa STKIP Muhammadiyah Muara Bungo - NURLEV AVANA (LP3M Universitas Muhammadiyah Muara Bungo, 2018)
Student learning outcomes look low. This is one factor that can show that students' mastery of mathematical concepts is still weak. This problem is estimated because learning is still centered on the lecturer, to overcome this problem is by implement learning aktif tipe Practice rehearsal pairs. This research aims to determine whether students’ conceptual understanding of statistical learning aktif tipe Practice rehearsal pairs type active learning is better than understanding students' concepts with conventional learning. This type of research is experimental research with the subject random design. The population in this research were STKIP students. The sampling technique is random, selected sample class. The instrument used in this research is the final test of learning in the form of essays. The data obtained were analyzed using normality test, homogeneity test and t-test. Based on the results of data analysis obtained the average learning outcomes of students who received treatment were 78,33 higher and the percentage of each indicator understanding the concept in the higher class. From the results of the t statistic test, it was obtained tcount = 2,15and ttable = 1,71, so that tcount > ttable and from MINITAB software obtained p-value = 0.010. It can be seen that p-value is smaller than α = 0.05. It can be concluded that the understanding of the concept of students who use Giving Question and Getting Answer type active learning is better.